Analyzing small RNA sequences from canine stem cell-derived extracellular vesicles primed with TNF-α and IFN-γ and exploring their potential in lung repair - Lee, Ji-Sun; Jeong, Yun-Ho; Kim, Yo-Han; Yun, Jang-Hyuk; Ahn, Jin-Ok; Chung, Jin-Young; An, Ju-Hyun (Frontiers in Veterinary Science, 2024)
Acute lung injury is an acute inflammation disorder that disrupts the lung endothelial and epithelial barriers. In this study, we investigated the extracellular vesicles (EVs) obtained via priming inflammatory cytokines such as tumor necrosis factor (TNF)-α and interferon (IFN)-γ on canine adipose mesenchymal stem cells in improving their anti-inflammatory and/or immunosuppressive potential, and/or their ability to alleviate lipopolysaccharide-induced lung injury in vitro. We also explored the correlation between epithelial-to-mesenchymal transition and the inflammatory repressive effect of primed EVs. Using small RNA-Seq, we confirmed that miR-16 and miR-502 significantly increased in EVs from TNF-α and IFN-γ-primed canine adipose mesenchymal stem cells. The pro and anti-inflammatory cytokines were analyzed in a lipopolysaccharide-induced lung injury model and we found that the EV anti-inflammatory effect improved on priming with inflammatory cytokines. EVs obtained from primed stem cells effectively suppress endothelial-to-mesenchymal transition in a lung injury model. Our results suggest a potential therapeutic approach utilizing EVs obtained from adipose mesenchymal stem cells primed with TNF-α and IFN-γ against lung inflammation and endothelial to mesenchymal transition.